2011
DOI: 10.1111/j.1365-2427.2011.02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Do birds of a feather disperse plants together?

Abstract: 1. Dispersal of propagules by waterbirds is thought to be important for wetland plants because of the abundance of birds and their frequent movements among aquatic habitats. Differences in bird characteristics (size, movement, feeding ecology) were expected to lead to different outcomes for plant dispersal. 2. We investigated heterogeneity in plant dispersal by ducks (Anas superciliosa, Anas gracilis, Anas castanea). We calculated the probability of transport of viable seeds by germinating propagules retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…At least one intact propagule was found in 37% of the ectozoochory samples. This proportion was approximately double that found in other recent studies investigating ectozoochory (Brochet et al ., ; Raulings et al ., ). External transport is usually a rare mechanism and is the dominant dispersal mode in only 5% of extant plant species (Sorensen, ); the high proportion of ‘positive’ ectozoochory samples was thus surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least one intact propagule was found in 37% of the ectozoochory samples. This proportion was approximately double that found in other recent studies investigating ectozoochory (Brochet et al ., ; Raulings et al ., ). External transport is usually a rare mechanism and is the dominant dispersal mode in only 5% of extant plant species (Sorensen, ); the high proportion of ‘positive’ ectozoochory samples was thus surprising.…”
Section: Discussionmentioning
confidence: 99%
“…() and Raulings et al . () provide Australian examples. In this article, we present the first quantitative analysis of the seed dispersal potential of waterbirds anywhere in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Darwin noticed in 'On the Origin of Species by means of Natural Selection' (Darwin, 1859) that the dispersal of seeds and vegetative fragments on the plumage and muddy feet of water-fowl can explain the wide range of some freshwater plants. By germinating propagules retrieved from feathers and feet (epizoochory) and the contents of the oesophagus, gizzard and lower gut (endozoochory), Raulings et al (2011) found that sedentary waterfowl are likely to have an important role in replenishing propagules and connecting aquatic metacommunities over small distances. Nomadic waterfowl may facilitate long-distance dispersal.…”
Section: Dispersal Mediamentioning
confidence: 99%
“…Some of this expansion can be attributed to the movement of seed through machinery, seed and feed . However, waterfowl have also been implicated, as they have demonstrated the ability to disperse wetland plant seeds over long distances . The abundance of waterfowl, their widespread distribution, as well as their high frequency of movement within and between habitats could prove crucial for the exchange of plant seed via waterfowl dispersal …”
Section: Introductionmentioning
confidence: 99%